1998
DOI: 10.1159/000028689
|View full text |Cite
|
Sign up to set email alerts
|

Shunt Revision by Coagulation with Retention of the Ventricular Catheter

Abstract: Intraluminal coagulation of a ventricular catheter followed by its removal and replacement is a technique used for proximal shunt revision. The authors describe experience leaving the original catheter in place when flow of CSF is established by the coagulation. Advantages of this modification include maintenance of ventricular access when the ventricles are small and the possibility of reducing the incidence of subsequent shunt obstruction by mitigating intraventricular hemorrhage caused by catheter removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The ensheathing reaction is believed to be a major contributing factor to decreases in indwelling device performance; however, the precise mechanisms that cause failure are not known [13][14][15][16][17][18][19][20][21][22][23]. For example, catheters implanted for draining excessive cerebrospinal fluid can be blocked by cellular ingrowth and may require frequent surgical revision [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ensheathing reaction is believed to be a major contributing factor to decreases in indwelling device performance; however, the precise mechanisms that cause failure are not known [13][14][15][16][17][18][19][20][21][22][23]. For example, catheters implanted for draining excessive cerebrospinal fluid can be blocked by cellular ingrowth and may require frequent surgical revision [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The ensheathing reaction is believed to be a major contributing factor to decreases in indwelling device performance; however, the precise mechanisms that cause failure are not known [13][14][15][16][17][18][19][20][21][22][23]. For example, catheters implanted for draining excessive cerebrospinal fluid can be blocked by cellular ingrowth and may require frequent surgical revision [22,23]. Increases in microelectrode impedance and loss of neuronal recording has been attributed to the encapsulating brain tissue response [13,20,21], and it has been suggested that glial encapsulation may reduce the permeability of microdialysis membranes and cell encapsulation devices [17][18][19]24].…”
Section: Introductionmentioning
confidence: 99%
“…[1111417] In most centers, the ratio of shunt revision to initial shunt surgery is 2:1. [2] Several studies have examined the surgical technique, [61216] shunt hardware, [315] and postoperative management [7813] of cerebrospinal fluid (CSF) shunting procedures in an attempt to improve shunt survival. However, only a few studies are available, which examine the consequences of replacing the entire shunt system versus a single component for the revision of a failed CSF shunt.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the surgical technique [10, 11, 12], shunt hardware [13, 14]and postoperative management [15, 16, 17]of CSF shunting procedures in an attempt to improve shunt survival. The effect of replacing the entire shunt system versus a single shunt component in the revision of failed CSF shunts has not been assessed.…”
Section: Introductionmentioning
confidence: 99%